Program Keselamatan dan Kesehatan Kerja ( Studi Kasus di di PT. PLN (Persero) Area Semarang ) - Yanuarius, William; Yuniningsih, Tri; Mustam, Mochammad (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
This research aims to analyze the Job Safety and Health Programs at PT. PLN (Persero) Area of Semarang and solutions for what has been done and that have not been implemented by the Committee for occupational safety and Health Program organiser Working in pt. PLN (Persero) Area of Semarang is not optimal. Locus were used in this study is in pt. PLN (Persero) Area of Semarang. This research uses qualitative research methods by using a descriptive approach. The subjects in this study consists of four main informant. Based on the results of the study showed that the implementation of the programme of safety and health at work PT. PLN (Persero) Semarang Area seen from such phenomena, non-physical state of the working environment is good, the physical state of a less good work environment, equipment and supplies and employees who have been good, and the physical condition and understanding of employees.Implementation of the programme of safety and health at work PT. PLN (Persero) it can be concluded that the Semarang Area are still less well, it is based on the phenomenonof building equipment and supplies and employees who are good, but in terms of procurement and practice in the field is still less than optimal.Conclusions in this study is the overall Program Workplace Health and Safety in pt. PLN (Persero) Semarang Area less well, and solutions that have not been done by the Committee organizers namely, Socialization of K3, K3 and infrastructure procurement, sanctions and rewards, education training and work tools, the increased budget, oversight and coordination between security officers with the Organizer, theevacuation route improvements and process simulation of evacuation and the solutions that have been implemented:, procurement clerks working tools, structuring the workspace employees, and the making of regulations for the employees. Based on these conclusions, the researchers recommend to PT. PLN (Persero) Area of Semarang to repair or improve the State of the physical work environment and psychological conditions and understanding of employees who were rated less well so that optimal performance can be achieved more.